Appearance of unplanned settlement as a reality in Medan City and surrounding area - Marpaung, Beny OY (IPTEK Journal of Proceedings Series, 2017)
Many unplanned settlements have appeared in Medan City and its surrounding areas. In general, people living in unplanned settlements have come from middle to lower class communities. The process and the components of unplanned residential areas arrangements are indeed related to social situation of their inhabitants. Social circumstances of unplanned settlements in Medan City and its surrounding areas offer a challenge to research about various forms of unplanned settlements; the pattern of buildings position and roads; and the people’s mindset in building the physical environment. The settlements are formed based on the inhabitants’ mentation which has its own characteristics. The study observes the possibility of spatial phenomena in a residential area that is formed unplanned. The location of this study is on unplanned settlements inside and outside Medan City. The research area is a settlement in Kelurahan Polonia and Silalas at Medan City and Besilam Babussalam Langkat which is located outside Medan City. This study uses qualitative methods to analyze and obtain discovery. Variables and data are determined based on the research of the theoretical basis. The conclusion from this study is the form of unplanned residential district tends to born from its inhabitants’ idea and the forming process of unplanned settlements really affects the development of the settlements itself.